Rumen Metagenomics and Its Implications in Animal Nutrition: A Review - Kolte, Atul P.; Dhali, A.; Malik, P. K.; Samanta, A. K.; Bhatta, Raghavendra (Indian Journal of Animal Nutrition, 2017)
The potential of metagenomics has paved way for studying yet to be cultured microbes, their abundance and functional capabilities in rumen ecosystem. Metagenomic techniques identified several new phyla in the domain bacteria. Rumen, being dominated by majority of yet to be cultured microbes, has not been aloof from application of metagenomics. The techniques available for studying microbial diversity without the need to cultur ethem are basically divided into low throughput and high throughput methods. The low throughputmethods are cheaper and do not require costly infrastructure but have limited power to resolve the microbial community members. On the contrary, the high throughput methods based on next generation sequencing technologies offer tremendous potential to investigate the microbial diversity and functional capabilities. Studies in rumen metagenomics has revealed discovery of several enzymes, antibiotic resistance genes, antibiotics, metabolic and xenobiotic degrading pathways apart form understanding the ecosystem and itseffect on nutrition and general health. The article discusses different techniques involved in rumen metagenomic investigation, applications in understanding microbial community dynamics under different dietary regimes, development and establishment of microflora, nutrition, methane mitigation, productivity etc.